Adopsi e-Government di Era Kebiasaan Baru - Kusumawati, Dyah; Saifudin, Saifudin (Program Studi Ilmu Komunikasi FBIK Unissula, 2023)
The aim of this paper is to investigate the factors that influence e-government adoption. This paper investigates the impact of trust in the Internet and trust in government on e-government adoption. The sample data used in this study were 126 respondents from 18 districts/cities in Central Java. SPSS was used to test the significance of the effect of the independent variable (trust in the internet and trust in the government) on the dependent variable (e-government adoption). The SPSS test results show that trust in the internet and trust in the government have a positive and significant effect on e-government adoption. Public service providers can predict the behavior of their users through this paper, while for academics, this paper can be used for further research by integrating trust as a predictor of adoption behavior. Empirically, this research is useful for increasing understanding of public service provider platforms in the communicative digital era.